Innovative processes and factors forming the mechanism of development of transport companies - Pakholka, Oleksandr Viktorovych (Global Prosperity, 2026)
Abstract. The article examines the modern features of innovation processes in the activities of transport companies and substantiates the factors that determine the formation of the mechanism of their innovative development. It is established that in modern conditions the innovative development of transport companies is associated with the transition from the fragmented implementation of individual technological solutions to the construction of a comprehensive innovation management system. It is determined that the main areas of innovation processes are the digitalization of operational activities, technological modernization of rolling stock and infrastructure, improvement of organizational and management models, development of human capital, as well as adaptation of transport systems to military risks and challenges of post-war recovery. The groups of factors that have a positive and negative impact on the innovative development of transport companies are systematized, namely: technical and economic, organizational and management, political and legal, socio-psychological and natural resource. Based on the expert-analytical approach, SWOT analysis and integrated assessment of innovativeness, the ranking of transport companies by the level of innovative potential is carried out. It has been proven that the formation of an effective mechanism for innovative development of transport companies requires a systematic combination of strategic management, digital technologies, investment support, and adaptive management solutions.